(untitled) (International Journal of Business, Economics and Management, 2018)
Since the last decade, rapid industry growth and booming world population increase the demand of water resource which brings out severe problems on water supply. In the Global Risk Report 2015 published by the World Economic Forum, water resource was ranked the greatest risk to the world. Taiwan is in 18th place in the UN global ranking among water-scarce countries. However, Taiwan has not established an integrated water resource information system to provide useful information to policy-makers and resource users. Therefore, this study adopts the international conceptual framework for water accounting to construct a water resource accounting information system tallied with Taiwan’s economic and policy conditions. The system is expected to provide useful information on water resource assets, liabilities, revenues and cost for economic sustainability. This study uses the case of Liyutan reservoir in Taiwan to illustrate the usefulness of the accounting information system which indicates new accounting research directions on water resource.